Geochemical and sulfur isotopic investigation of black shales from the Paja Formation (2025)
The Paja Formation from the Lower Cretaceous period is exposed in the Eastern Cordillera of Colombia. Specifically on the region of Alto Ricaurte in the Department of Boyacá, near Villa de Leyva, in Vereda El Roble, a black shale profile has been sampled and analyzed. Sulfur isotope analysis revealed δ34SSulfate values ranging from -5‰ to -1‰, significantly lower than typical Cretaceous seawater values, and δ34S Sulfide values ranging from -5‰ to 8‰. These results indicate that the geochemical and isotopic composition of the black shale profile reflects an interplay between paleoenvironmental conditions, and secondary diagenetic processes. Mo/TOC, Fe/Al, TOC/TS, K2O/Al2O3 ratios and high concentrations of V, Cr, Ni, P and Al suggest the Paja Sea was a moderately restricted basin, characterized by intense chemical weathering, weakly to moderately sulfidic bottom waters, and enhanced primary productivity in oxygenated surface waters. Uranium concentrations, along with Th/U and Zr/Ti ratios indicate a dual sediment provenance: weathering from a felsic continental source and input from a mafic volcanic arc setting. The sulfur isotope anomalies are associated to local depositional conditions and post depositional alteration by hydrothermal fluids, evidenced by the presence of gypsum, pyrite, sulfide oxidation and correlations between TOC/ δ13Corg ratios.